2016
DOI: 10.1111/pde.12800
|View full text |Cite|
|
Sign up to set email alerts
|

Papular Epidermal Nevus with Skyline Basal Cell Layer (PENS): Three New Cases and Review of the Literature

Abstract: The probability of having extracutaneous manifestations is 6.3 times as great in individuals with more than four lesions. Therefore these patients may need closer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Even though not clearly stated in the abovementioned article, some central, clear, pink discoloration, as reported in our case, is also observable in the image that Luna et al published (2).…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Even though not clearly stated in the abovementioned article, some central, clear, pink discoloration, as reported in our case, is also observable in the image that Luna et al published (2).…”
Section: Discussionsupporting
confidence: 45%
“…In the present case, all the lesions shared a common pattern, with slight differences according to their dimension. We hypothesize that these small Luna et al (2) first reported a single-case dermoscopic picture of PENS. They detected some characteristics similar to those seen in epidermal nevi: a nonmelanocytic pseudonetwork with exophytic, papillomatous structures with milia-like cysts and globules.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In conclusion, the present cases add a new piece to the still incompletely understood puzzle of PENS and PENSS. Even though, to the best of our knowledge, only a few cases of PENS have been reported, it is likely that it is underdiagnosed because it is often misdiagnosed and mistaken for nonspecific epidermal nevus, especially because the histopathology has only recently been recognized as being unique for this diagnosis. We hope that awareness of this lesion will lead to more frequent diagnosis and better understanding of clinical associations and PENSS.…”
Section: Discussionmentioning
confidence: 99%
“…Papular epidermal nevus with “skyline” basal cell layer (PENS) is a recently described keratinocytic nevus . Recently, PENS has been reported in association with extracutaneous involvement, and Tadini and colleagues proposed the term PENS syndrome (PENSS) to indicate a neurocutaneous syndrome characterized by the presence of PENS and different neurologic symptoms that seem to improve during infancy and adolescence . It has been postulated that PENSS occurs more frequently in individuals with more than four PENS lesions .…”
Section: Introductionmentioning
confidence: 99%